Violence against Healthcare Workers during the COVID-19 Pandemic: A Review of Incidents from a Lower-Middle-Income Country - Omaima Anis Bhatti (Ubiquity Press, 2021)
Background: Healthcare workers (HCWs) across the globe have met tremendous challenges during the COVID-19 (coronavirus disease 2019) pandemic, such as shortages of personal protective equipment, extensive work hours, and constant fear of catching the virus or transmitting it to loved ones. Adding on to the already existing burnout, an increase in incidents of violence and aggression against HCWs was seen in Pakistan and globally. Objectives: Primarily to review cases of violence against HCWs in Pakistan, highlighting and comparing the instigating factors seen within the country and globally. Secondly, to enlist possible interventions to counter workplace violence in healthcare during a pandemic and in general. Methods: Incidents of violence towards HCWs in Pakistan during the COVID-19 pandemic occurring between April 7, 2020, and August 7, 2020, were included. The incidents reported from local newspapers were reviewed. Findings and Conclusion: A total of 29 incidents were identified, with perpetrators of violence most commonly being relatives of COVID-19 patients. Most frequent reasons included mistrust in HCWs, belief in conspiracy theories, hospitals’ refusal to admit COVID-19 patients due to limited space, COVID-19 hospital policies, and the death of the COVID-19 patients. Protests by doctors and other HCWs for provision of adequate PPE, better quarantine conditions for doctors with suspected COVID-19, and better compensation for doctors on COVID-19 patient duty resulted in police violence towards HCWs. To avoid such incidents in the future, institutions, healthcare policymakers, media organisations, and law enforcement agencies must work together for widespread public awareness to counter misconceptions and to exhibit responsible journalism. In hospitals, measures such as de-escalation training and increased security must be implemented. Furthermore, law enforcement agencies must be trained in non-violent methods of crowd dispersal and control to manage peaceful protests by HCWs over legitimate issues.